(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions defined from a generalized topological space into a bitopological space, called upper μ(σ_1,σ_2)-continuous multifunctions and lower μ(σ_1,σ_2)-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper μ(σ_1,σ_2)-continuous multifunctions and lower μ(σ_1,σ_2)-continuous multifunctions are discussed.